2001
DOI: 10.1111/0023-8333.00163
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal Analysis of Formulation Processes in L1 and L2 Writing

Abstract: This cross-sectional study used verbal protocol analysis to compare the temporal distribution of formulation processes of Spanish EFL writers composing L1 and L2 argumentative texts. We studied three groups at different levels of L2 proficiency. Results showed the same total formulation time regardless of whether participants wrote in L1 or L2. L2 proficiency, however, affected times. Higherproficiency participants devoted less time to formulation, concentrated formulation in the central stages of composing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 49 publications
(76 reference statements)
2
56
1
Order By: Relevance
“…For example, a number of factors including student writers' L2 proficiency might influence students' level of knowledge and writing in English [19]. In a similar vein, it has been revealed that L2 higher proficiency participants devoted less time to formulation, concentrated formulation in the central stages of composing in English [39]. In addition, it is proved that secondlanguage proficiency is a significant factor in developing the overall quality of students' written products [15].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of factors including student writers' L2 proficiency might influence students' level of knowledge and writing in English [19]. In a similar vein, it has been revealed that L2 higher proficiency participants devoted less time to formulation, concentrated formulation in the central stages of composing in English [39]. In addition, it is proved that secondlanguage proficiency is a significant factor in developing the overall quality of students' written products [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cumming 1989;Manchón et al, 2009;Sasaki, 2000Sasaki, , 2002 or (b) with reference to just one macro-writing process, be this planning (cf. Akyel, 1994;Manchón & Roca de Larios, 2007a), formulation (e.g., Chenoweth & Hayes, 2001;Roca de Larios et al, 2001;Zimmermann, 2000), or revision (e.g., Porte, 1995Porte, , 1996Porte, , 1997Sengupta, 2000;Takagaki, 2003). Some taxonomic approaches in the general literature of strategies have been used in the classification of writing strategies (see the review in Manchón et al, 2007), and a more recent trend in research has been framed in theories of self-regulation (e.g., Csizer & Tang, 2015).…”
Section: Strand 1: Strategy Use -Mediating Factors and Effectsmentioning
confidence: 99%
“…Advanced and emergent planning (i.e. thinking about the content in advance or while writing) are two types of control mechanisms, while repetitions and rereadings of the text already composed are problem-solving mechanisms, which serve to make up for lack of linguistic knowledge, as pointed out by a number of investigations with EFL writers (Roca de Larios et al, 2001;Wolfersberger, 2003). Repetitions are used for compensating for the limited capacity of the working memory and rereadings for revision, planning or transcription purposes (Manchó n, 2001, p. 56).…”
Section: Theoretical Frameworkmentioning
confidence: 99%